O espaço territorial na ótica do design estratégico: construção de cenários urbanos para a cidade de Canoas-RS - Cruz, Ângelo Fernando da (Universidade do Vale do Rio dos Sinos, 2012)
This work had dedicated to investigate the nature of urban spaces from the perspective of strategic design. With this proposal, the design becomes to be considered with a focus on the territory, specifically about the city and its context within an complex and conurbation area that sets the metropolitan areas, having the city of Canoas as the specific object of this study, a city located in the metropolitan area Porto Alegre. This work of the discussion of the fundamentals and concepts that characterize the territories and urban spaces, from a theoretical basis of the authors that reference and theme. After this, is brought to discussion, the conceptual foundations of strategic design and the context of the territory from its perspective. Thus, the territory is seen and described as a commodity, and, under this condition, is developed the application of two metology for data collection, a qualitative and another one quantitative method allowing an immersion in the complex universe of perceptions and views of the set of actors who are part of the social universe of Canoas. The Analysis and interpretation of this data set allows to build a reference base for the realization of a stage of experimentation in which, through a design workshop, future scenarios are created for the city.
Keywords: Cidade; Espaço Urbano; Design estratégico; Laddering; Cenários territoriais; City; Urban area; Strategic design; Territorial scenarios; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial